“The Past Undetonated”: Nostalgia and Storytelling in Philip Roth’s American Pastoral - Tanguy Bérenger (Transatlantica)
This article explores the nostalgia for 1940s Newark exhibited by Nathan Zuckerman in Philip Roth’s American Pastoral. In the first part of the novel, the narrator presents an idealized version of his hometown characterized by a tight-knit community and a clear sense of order, contrasting starkly with his present situation. Although Zuckerman acknowledges the illusory nature of his fantasy, he cannot help but indulge in it. This ambivalent reaction is actually the creative spark from which the main narrative emerges.